Peran Kepemimpinan Kepala Desa Dalam Meningkatkan Efektivitas Kerja Pegawai Pada Kantor Desa Ba`Ba Tapua Kecamatan Matangnga Kabupaten Polewali Mandar - Steviayu Lestari; Nurman Nurman; Agung Widhi Kurniawan; Tenri Sayu Puspitaningsih Dipoatmodjo; Muhammad Ilham Wardhana Haeruddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this research is to determine the leadership role of the Village Head in improving the work effectiveness of employees at the Ba`ba Tapua Village Office, Matangnga District, Polewali Mandar Regency. With this type of qualitative research. Data collection techniques are carried out through observation, interviews and documentation. By determining the key informant, namely the Village Secretary, the main informant, namely the Section Head, and the supporting informant, namely one of the Hamlet Heads. The research results show that the village head's leadership in improving employee work effectiveness in its implementation is quite good as seen from the aspects of his open leadership, good communication with his employees, happy to accept suggestions from employees, providing motivation, direction and providing training to employees, as well as decision making which is held through deliberation. However, employee work effectiveness is still lacking because it is also influenced by other things such as the work environment.